The Kyai Langgar as an Agent of Islamic Education: A Study on the Transformation of Roles in Ngepoh Village - Mukarromah, Lu’luil; Prasetiya, Benny; Masuwd, Mowafg (Universitas Muhammadiyah Sidoarjo, 2024)
This research explores the transformation of Kyai Langgar's role in spreading religious values ​​amidst ever-developing social dynamics. Using a qualitative approach, this research reveals how Kyai Langgar, as a spiritual leader, not only plays a role as a religious teacher, but also as an agent of significant social change. Kyai Langgar is active in various religious activities such as congregational prayers, regular recitations, and reciting the Koran, and plays an important role in developing the younger generation and maintaining social harmony. This research also identifies the challenges faced by Kyai Langgar, including the influence of modernization, social and cultural diversity, and the use of technology and social media. Despite facing these various challenges, Kyai Langgar remains consistent in spreading the values ​​of religiosity with an inclusive approach that focuses on social welfare. This research emphasizes the important role of Kyai Langgar in maintaining morality and social stability amidst the modernization process. In addition, this research recommends increasing the involvement of Kyai Langgar in social and educational development programs at the village level to improve the quality of life of the community. These findings provide new insight into how Kyai Langgar adapts to social change, reflecting the combination of tradition and modernity in the context of Indonesian society's religiosity. Highlights: Kyai Langgar serves as a spiritual leader and agent of social change in Ngepoh Village. Adaptation to modern challenges includes the use of technology and engagement in community-based initiatives. The role of Kyai Langgar extends beyond religious duties to encompass education, social welfare, and political involvement. Keywords: Transformation of Kyai Langgar, Religious Values, Social Dynamics